Dual Axis Solar Tracker with Arduino-Based Voltage Monitoring - Fatih Zharfa Athara; Faiz Athalla Putra; Marsellinus David Praskadana; Arief Arfriandi (Politeknik Negeri Semarang, 2026)
This research develops an Arduino-based dual-axis solar tracker system with real-time current and voltage monitoring. The system uses an LDR sensor to detect light direction and a servo motor to adjust the panel orientation on two axes, so that the radiation reception angle remains optimal. Electrical parameters are measured using an INA219 sensor and displayed through a display media. The research method includes design, implementation, and testing by comparing the performance of static panels and the tracking system. The results show that the solar tracker system increases the output voltage compared to static panels. The calculation produces a fill factor of 0.79 and an efficiency of 15.31%, indicating improved energy absorption performance. The developed system is effective in optimizing solar panel output and provides monitoring data for performance evaluation.